Pengaruh Akuntabilitas, Transparansi, Partisipasi, Pengawasan, Dan Pemahaman Akuntansi Terhadap Kinerja Anggaran Dana Desa Berbasis Value For Money - Pramita, Yulinda Devi; Filiana, Ilma; Maharani, Betari (Jurnal Riset AKuntansi dan Bisnis, 2024)
This research aims to test and analyze empirically the influence of accountability, transparency, participation, supervision and understanding of accounting on the performance of value for money based village fund budgets (empirical study in villages throughout Tempuran sub-district, Magelang district). The data used in this research is primary data. The population of this study was 15 village offices in Tempuran District, Magelang Regency. Meanwhile, the samples in this study were the village head, financial head, Head of Welfare, Head of Development, Head of Hamlet. The sampling technique is using a purposive sampling method. The number of samples used was 15 village offices with a total of 170 respondents. The analytical method used in this research was multiple linear regression analysis. The results of this research show that accountability, transparency, participation, supervision and understanding of accounting have a positive effect on the performance of village fund budgets based on value for money.